Mapping constitutionally safeguarded judicial independence: A global survey - Bernd Hayo; Stefan Voigt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
De jure judicial independence (JI) is the single most important predictor of de facto JI. In this paper, we describe under what conditions countries are likely to include JI in their constitutions. We describe and analyze both their original choice in this regard as well as change over time using a newly constructed dataset comprised of 100 countries and covering the years between 1950 and 2005. Three results stand out. First, legal origins do have an impact on the likelihood of explicitly anchoring JI in the constitution: countries belonging to the common law tradition are less likely to implement JI in their constitutions (and those with a socialist tradition are more likely to do so). Correspondingly, former British colonies are less likely to address JI explicitly as are states in the Caribbean. Second, religion has a significant impact on whether JI is included in the constitution: societies experiencing a high level of religious fractionalization are not only less likely to anchor JI in their constitutions, but are also less likely to change their constitutions in that direction later on. Finally, Muslim countries are more likely to include mention of JI, whereas Protestant countries are less likely to do so. Third, the distribution of resources within societies has important and largely unexpected effects: a higher percentage of family farms, a wider distribution of education, and a higher percentage of urban dwellers are all connected with a lower likelihood of JI being mentioned in the constitution.
Keywords: K10; N40; 330; judicial independence; constitutional choice; constitutional change; Gerichtsbarkeit; Justiz; Gewaltenteilung; Verfassungsreform; Verfassungsökonomik; Schätzung; Welt